2019
DOI: 10.29333/ejgm/110172
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid disease among adults and children: it is time to worry!

Abstract: Background: Hydatid disease is a public health issue as it continues to produce substantial morbidity and mortality. The most common affected organ among adults is the liver and among children, is the lungs. Its treatment includes medical therapy, surgical intervention or percutaneous drainage. We aimed to identify the clinical, therapeutic and evolutionary features of hydatid cyst among adults and children. Method: We conducted a retrospective study including all patients hospitalized in Pediatric and Infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
(24 reference statements)
3
1
0
Order By: Relevance
“…In the present study, 73.9% of patients lived in villages, which was in line with previous studies (63.1 to 83%) (34,42). Although in this study, the rate of patients with CE in rural areas was three times higher than in urban areas, we should inform the local health organizations about the burden of CE in both urban and rural regions to plan educational programs for awareness among local people about the preventive strategies to control CE locally.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, 73.9% of patients lived in villages, which was in line with previous studies (63.1 to 83%) (34,42). Although in this study, the rate of patients with CE in rural areas was three times higher than in urban areas, we should inform the local health organizations about the burden of CE in both urban and rural regions to plan educational programs for awareness among local people about the preventive strategies to control CE locally.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that 72% of the patients had a history of contact with animals. Similar to our results, in other studies, the rate of contact with animals was reported between 59.5% and 68.4% (32,34,42). The high rate of close contact in this study highlighted that one of the preventive strategies for CE in this region is to keep children away from untreated animals and refrain from keeping animals indoors.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations